2017
DOI: 10.1016/j.jaut.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping and auto-antibody production by liver-infiltrating B cells in primary sclerosing cholangitis and primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are immune-mediated biliary diseases that demonstrate prominent and restricted genetic association with human leukocyte antigen (HLA) alleles. In PBC, anti-mitochondrial antibodies (AMA) are specific and used as diagnostic biomarkers. PSC-relevant auto-antibodies remain controversial despite a distinct HLA association that mirrors archetypical auto-antigen driven disorders. Herein, we compared antibody-secreting B cells (ASCs) in PSC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…An insignificantly abundant clonal diversity in the infiltrating B cell repertoire of PBC relative to ALD patients was observed from all perspectives (Fig. ), which conforms with more infiltrating B lymphoplasmacytes in the end‐stage PBC patients …”
Section: Resultssupporting
confidence: 60%
“…An insignificantly abundant clonal diversity in the infiltrating B cell repertoire of PBC relative to ALD patients was observed from all perspectives (Fig. ), which conforms with more infiltrating B lymphoplasmacytes in the end‐stage PBC patients …”
Section: Resultssupporting
confidence: 60%
“…The pathogenic role of B cells in PSC‐IBD is poorly established as a broad spectrum of non‐specific autoantibodies to biliary and colonic epithelial antigens, neutrophil granulocytes (perinuclear anti‐neutrophil cytoplasmic antibodies [pANCA]), and several ubiquitous self‐proteins appear in affected individuals . Although disease‐specific autoantibodies have not been identified in sera, we have demonstrated that B cells infiltrating liver explants of patients with PSC‐IBD can be isolated and cultured to produce a diverse repertoire of autoantibodies whose specificities may point toward relevant self‐antigens or cross‐reactive exogenous targets . Thus, a better appreciation of B‐cell reactivities in PSC‐IBD may uncover useful biomarkers similar to patients with primary biliary cholangitis (PBC) where liver‐infiltrating B cells produce disease‐associated anti‐mitochondrial antibodies to pyruvate dehydrogenase complex‐E2 .…”
mentioning
confidence: 99%
“…Although disease‐specific autoantibodies have not been identified in sera, we have demonstrated that B cells infiltrating liver explants of patients with PSC‐IBD can be isolated and cultured to produce a diverse repertoire of autoantibodies whose specificities may point toward relevant self‐antigens or cross‐reactive exogenous targets . Thus, a better appreciation of B‐cell reactivities in PSC‐IBD may uncover useful biomarkers similar to patients with primary biliary cholangitis (PBC) where liver‐infiltrating B cells produce disease‐associated anti‐mitochondrial antibodies to pyruvate dehydrogenase complex‐E2 . A better understanding of B‐cell reactivities in PSC‐IBD may also help define patient subgroups, including specific genetic and disease characteristics of pANCA‐positive versus seronegative patients …”
mentioning
confidence: 99%
“…Recent efforts of characterizing disease-associated antibodies using liver-resident B cells from PSC patients could lead to the identification of relevant autoantibodies, but further work is needed to validate such methodologies [85] . In 30-80% of cases, PSC strongly associates with inflammatory bowel disease (PSC-IBD) suggesting that the gut-liver axis contributes to the pathogenesis of PSC, including lymphocyte migration and the exposure to shared antigens between the gut and liver [86] .…”
Section: Hla Associations For Immune-mediated Liver Diseases Point Tomentioning
confidence: 99%